The Effects of Long-Term Graft Preservation on Intraoperative Hemostatic Changes in Liver Transplantation. Issue 4 (1994) - Bakker, C. Minke; Blankensteijn, Jan D.; Schlejen, Peter; Porte, Robert J.; Gomes, Maria J.; Lampe, Harald I. H.; Stibbe, Jeanne; Terpstra, Onno T.
Abstract : We compared hemostatic changes during OLT and HLT after various periods of graft storage, to investigate whether the host liver in HLT protects the recipient from hemostatic deterioration induced by severe graft storage damage. In particular, the mechanism of fibrinolytic deterioration was investigated. The effect of prostaglandin E1 (PGE1 ) on these parameters was also studied. Material and Methods : 69 pigs underwent either OLT (N = 32) or HLT (N = 37) with a graft stored for 2 hr (N = 31), 24 hr (N = 16), 48 hr (N = 7), or 72 hr (N = 15). PGE1 was given intravenously to both donor and recipient animals and was added to the preservation and flushing solutions. Fibrinolysis (euglobulin clot lysis time, t-PA activity and α 2 -antiplasmin) and coagulation parameters (activated partial thromboplasmin time, prothrombin time, fibrinogen and platelet count) were measured at several intervals during transplantation. Statistics : Univariate non-parametric tests were used for analysis of coagulation and fibrinolysis parameters. For the three main variables- i.e., the type of transplantation, the use of PGE1, and the preservation time, multiple regression analysis was performed. Results : Fibrinolytic activity increased during the anhepatic period of OLT. Graft reperfusion was followed by a rise in t-PA in both OLT and HLT. In HLT, t-PA quickly returned to normal, whereas a continuous increase was found in OLT. The coagulation parameters, in turn, remained unchanged during the anhepatic period and deteriorated in OLT compared to HLT. The duration of graft storage was directly related to the severity of the hemostatic changes, although this effect was more apparent in OLT than in HLT. Conclusions : Changes in hemostasis are more pronounced in OLT than in HLT. This suggests that the host liver protects the recipient from the effects of graft storage damage, even after long preservation times. Early postreperfusion fibrinolytic activity was presumably due to t-PA release from the graft both in OLT and HLT. The further rise t-PA in OLT might be caused by the release of cytokines from the graft, that subsequently evoke endothelial t-PA release. In HLT, t-PA and cytokines may be cleared by the native liver. No positive or negative effect of PGE1 on coagulation or fibrinolysis parameters was noticed.